Evaluating the effectiveness and limitations of online health information tools in assessing the quality of medication-related content - Alhlayl, Adel S.; Alzghaibi, Haitham A. (Frontiers in Public Health, 2025)
IntroductionThe internet has become a primary source of information on medicines, yet the quality of this information is inconsistent. Despite the proliferation of web-based resources, limited research has specifically examined the reliability of online information on medicines. The variability in quality can be attributed to the recent shift toward digital information-seeking and the absence of specialized tools designed to assess the quality of medication-related information online.AimTo evaluate the quality of information about Amitriptyline available on websites using three well-established, generic evaluation tools—HONcode, DISCERN, and JAMA—compared against the domain-specific Keystone action plan criteria.MethodsAdopting an evaluative research design, this study utilized the aforementioned four assessment tools to collect and analyze data. Four independent assessors were recruited to evaluate the quality of the information on selected websites.ResultsA Google search using “Amitriptyline” identified 30 websites for the study sample. Reliability analysis using Cronbach’s alpha, the Inter-Class Correlation coefficient, and Kendall’s rank-order correlation coefficient revealed that the Keystone criteria demonstrated the highest internal consistency and reliability compared to DISCERN, HONcode, and JAMA.ConclusionThis study indicates that the Keystone action plan criteria may serve as a reliable, domain-specific tool for evaluating medicines information on websites. The results underscore the importance of specialized assessment criteria for online medication information, as they provide more consistent and accurate evaluations compared to generic tools.